Bridging Technology and Values: Opportunities and Barriers to Artificial Intelligence–Supported Meaningful Learning in Elementary School - Yeni Erita; Aisyah Anggraeni; Risda Amini; Silvi Hevria (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the integration of Artificial Intelligence (AI)-supported meaningful learning into elementary social studies education in Indonesia, with a focus on enhancing students’ social skills and moral sensitivity. Grounded in qualitative research design, data were collected through classroom observations, interviews with teachers, and the analysis of learning activities in selected public elementary schools. Findings reveal that AI-based learning platforms such as adaptive discussion forums, collaborative digital projects, and interactive simulations encourage students to actively engage in teamwork, communication, and problem-solving. Moreover, AI-assisted scenarios that present moral dilemmas and provide reflective feedback foster students’ ability to recognize ethical values, practice empathy, and develop moral reasoning. The study highlights how AI can serve not merely as a technological tool, but as a pedagogical partner that enriches the value-laden nature of social studies. However, challenges such as limited digital infrastructure, uneven teacher readiness, and educational–cultural considerations in Indonesia remain significant barriers to sustainable implementation. Overall, the integration of AI-supported meaningful learning demonstrates promising potential to strengthen competency skills and moral awareness among young learners, while also offering insights for curriculum reform and policy development in the Indonesian context.